2012
DOI: 10.1038/cgt.2012.45
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of genetically engineered stem cells expressing cytosine deaminase and interferon-β via their tumor tropism to selectively target human hepatocarcinoma cells

Abstract: Stem cells have received a great deal of attention for their clinical and therapeutic potential for treating human diseases and disorders. Recent studies have shown that it is possible to genetically engineered stem cells (GESTECs) to produce suicide enzymes that convert non-toxic prodrugs to toxic metabolites, selectively migrate toward tumor sites and reduce tumor growth. In this study, we evaluated whether these GESTECs are capable of migrating to hepatocarcinoma cells and examined the potential therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The CE gene product metabolically converts the prodrug CPT-11 into SN-38 which induces apoptosis in cancer cells (16). GEPT systems seem to reduce the toxicity of anticancer drugs in normal tissues compared to conventional therapies (17). However, these systems are hindered by the low gene transfer efficiency of viral vectors and the inability to specifically target cancer cells (18).…”
Section: Additional Effects Of Engineered Stem Cells Expressing a Thementioning
confidence: 99%
“…The CE gene product metabolically converts the prodrug CPT-11 into SN-38 which induces apoptosis in cancer cells (16). GEPT systems seem to reduce the toxicity of anticancer drugs in normal tissues compared to conventional therapies (17). However, these systems are hindered by the low gene transfer efficiency of viral vectors and the inability to specifically target cancer cells (18).…”
Section: Additional Effects Of Engineered Stem Cells Expressing a Thementioning
confidence: 99%
“…The tumor tropic property of NSCs and their migratory ability are critical for targeted delivery of anticancer agents [20][21][22][23][24]. These properties give the NSCs selectivity, specificity [25], and ability to track the invasive tumor cells in vivo [26].…”
Section: Intracranial Delivery Of Therapeutic Nscs Secreting Anti-hermentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the sixth most common cancer and third most common cause of cancer-related death in the world [55]. For treating HCC in a xenograft SCID mouse model, Yi et al compared NSCs with HB1.F3.CD and HB1.F3.CD.IFN-β cells expressing the CD and/or interferon-beta (IFN-β) gene [56]. Results of this experiment showed that NSCs expressing the therapeutic genes have the potent advantage of selective migration toward HCC cells in vivo .…”
Section: Nsc-based Therapies For Treating Various Human Primary Tumormentioning
confidence: 99%
“…After 8 weeks, mice in the negative control group (without stem cells or prodrug) bearing tumors reached the endpoint of ethical death. However, tumor growth in animals treated with the HB1.F3.CD or HB1.F3.CD.IFN-β cells was inhibited approximately 40-50% compared to the control group [56]. Additionally, fluorescence prestained NSCs were detected in HCC tumor mass of animal models.…”
Section: Nsc-based Therapies For Treating Various Human Primary Tumormentioning
confidence: 99%